Post-Occupation Evaluation of Industrial Heritage Transformation into a Mixed-Mode Park Within the Context of Urban Renewal: A Case Study of Hebei, China - Xiaowei Chen; Yijing Chen; Yuchen Liu (Buildings)
In recent years, the in-depth implementation of China’s “shifting from secondary industries to tertiary industries” policy, coupled with the accelerating pace of urban renewal, has positioned the transformation and reuse of industrial heritage as a pivotal approach to enhancing urban spatial quality and fostering cultural continuity. This paper focuses on three mixed-mode industrial heritage transformation parks in Hebei Province: Dahua, Miansan, and Shimeiji. Based on existing research and practical circumstances, an evaluation system encompassing six dimensions and 18 indicators is established. On this basis, a questionnaire survey was conducted, including two parts: a satisfaction questionnaire and a Kano model questionnaire. According to the obtained data, the use of the park after completion was evaluated and the existing problems of the mixed-mode industrial heritage renovation park were summarized comprehensively. The research finds out the shortcomings of the commonalities and differences of mixed-mode industrial heritage parks, finally putting forward optimization suggestions for the problems, in order to provide theoretical reference and practical guidance for the renovation projects of the same type of industrial heritage in the urban renewal stage.